2008
DOI: 10.1152/ajpregu.00687.2007
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced muscle fatigue occurs in male but not female ASIC3−/− mice

Abstract: Burnes LA, Kolker SJ, Danielson JF, Walder RY, Sluka KA. Enhanced muscle fatigue occurs in male but not female ASIC3Ϫ/Ϫ mice. Am J Physiol Regul Integr Comp Physiol 294: R1347-R1355, 2008. First published February 27, 2008 doi:10.1152/ajpregu.00687.2007.-Muscle fatigue is associated with a number of clinical diseases, including chronic pain conditions. Decreases in extracellular pH activates acid-sensing ion channel 3 (ASIC3), depolarizes muscle, protects against fatigue, and produces pain. We examined wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 69 publications
1
41
0
Order By: Relevance
“…Hindpaw and forepaw grip force was tested before and after 5 days (n ϭ 4) or 8 wk (n ϭ 8) of running wheel activity and compared with sedentary mice (n ϭ 8) as previously described (6). The mice were familiarized twice per day for 2 days to the apparatus by performing the grip force task (San Diego Instruments, San Diego, CA, http://www.sandiegoinstruments.com).…”
Section: Motor Testingmentioning
confidence: 99%
“…Hindpaw and forepaw grip force was tested before and after 5 days (n ϭ 4) or 8 wk (n ϭ 8) of running wheel activity and compared with sedentary mice (n ϭ 8) as previously described (6). The mice were familiarized twice per day for 2 days to the apparatus by performing the grip force task (San Diego Instruments, San Diego, CA, http://www.sandiegoinstruments.com).…”
Section: Motor Testingmentioning
confidence: 99%
“…Also, the cytoplasmic level of testosterone from male asic3 -/-mice was significantly lower than that in WT male mice and was similarly low in female WT mice. These data suggest that both ASIC3 and testosterone are necessary for protecting against muscle fatigue (61). Moreover, differences in the expression of ASIC3 and the development of exercise-induced fatigue could explain the female predominance in clinical syndromes of pain that include muscle fatigue (61 Review are unclear but could involve decreases in extracellular pH, activation of ASIC3 channels, and subsequent muscle depolarization, which protects against fatigue or causes pain sensation.…”
Section: Muscle Nociception and Fatiguementioning
confidence: 99%
“…These data suggest that both ASIC3 and testosterone are necessary for protecting against muscle fatigue (61). Moreover, differences in the expression of ASIC3 and the development of exercise-induced fatigue could explain the female predominance in clinical syndromes of pain that include muscle fatigue (61 Review are unclear but could involve decreases in extracellular pH, activation of ASIC3 channels, and subsequent muscle depolarization, which protects against fatigue or causes pain sensation. Moderate exercise increases the expression of asic3 mRNA in chronic fatigue syndrome patients but not in normal subjects (62).…”
Section: Muscle Nociception and Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Cuesta et al [17] showed the presence and localization of different ASICs in the human healthy intervertebral disk, and an increased expression of ASICs in the degenerated intervertebral disk, indicating that ASICs may be involved in intervertebral disk degeneration. In this study, we investigated two ASIC subunits (ASIC1 and ASIC3) in nucleus pulposus cells of the human intervertebral disk, which were reported to be relevant for the function of connective tissues including bone and cartilage [18][19][20]. Uchiyama et al [21] confirmed the presence of ASIC3 subunit in nucleus cells of the intervertebral disk.…”
Section: Discussionmentioning
confidence: 86%